2010
DOI: 10.3748/wjg.v16.i34.4321
|View full text |Cite
|
Sign up to set email alerts
|

HCV genotype distribution and possible transmission risks in Lahore, Pakistan

Abstract: An increase in genotypes 1a and 4a suggest migration of people, possibly from Balochistan and the northern war-zone area. Government should focus on public education regarding infection routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
44
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 35 publications
19
44
3
Order By: Relevance
“…The most frequent genotype of HCV circulating was 3a 45%, followed by unknown genotype 20%; HCV genotype with 3b 20%, with 2a 10% and 1a 5%.The HCV genotype 1a, 4a, 5a, 6a and 2b were not observed among the 20 studied cases. In the present study the HCV genotype observed in some respect varies from the previous study, but common finding was that the most common genotype (45%) was 3a, while previously Hakim et al, 2008, Idrees and, and Ahmad et al, 2010, have reported it as 51%, 49.05% and 55.09% respectively [36,37,38,39]..…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The most frequent genotype of HCV circulating was 3a 45%, followed by unknown genotype 20%; HCV genotype with 3b 20%, with 2a 10% and 1a 5%.The HCV genotype 1a, 4a, 5a, 6a and 2b were not observed among the 20 studied cases. In the present study the HCV genotype observed in some respect varies from the previous study, but common finding was that the most common genotype (45%) was 3a, while previously Hakim et al, 2008, Idrees and, and Ahmad et al, 2010, have reported it as 51%, 49.05% and 55.09% respectively [36,37,38,39]..…”
Section: Discussioncontrasting
confidence: 52%
“…Cytotoxic T-lymphocytes (CTLs or CD8) cells have evoke a potential factor in the development of chronic infection of HCV [35]. Immunologic disorder plays an important role in chronic hepatitis C which is approximately 38% [36]. Due to this reason our study showed that adults of age below 20 years were less infected due to strong immunity as compared to the age above 20 years.…”
Section: Discussionmentioning
confidence: 68%
“…These genotypes were developed from the high degree of HCV sequence variation. There are six major HCV genotype groups and seventy subgroups [1]. In certain geographic areas Genotypes 1, 2 and 3 are more prevalent compared to 4, 5 and 6 which are present in other geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-established that HCV genotype 3a is highly prevalent in Pakistani population (9,11,14). On the other hand, a single study revealed that 1a genotype has a higher frequency in Balochistan (7).…”
Section: Discussionmentioning
confidence: 99%